2002
DOI: 10.1111/1467-8276.00041
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Growth and Environmental Regulation in Mexican and U.S. Food Manufacturing

Abstract: Many argued during the NAFTA debate that trade liberalization would favor Mexican over U.S. food processors, especially because of lax environmental laws south of the border. We find through an examination of profit functions that productivity growth in Mexico has outstripped that in the United States, suggesting free trade indeed will benefit Mexican suppliers. U.S. pollution regulations have had no impact on the profitability or productivity of U.S. food manufacturing. In contrast, Mexico's swiftly rising en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(117 citation statements)
references
References 20 publications
3
110
0
4
Order By: Relevance
“…Another strand of studies in the distance function framework is stochastic production frontier analysis (SFA), which includes a stochastic error term in the computation of the production possibility frontier, e.g., [8,18]. Finally, total factor productivity (TFP) is used in numerous studies [2,6,[19][20][21][22][23][24][25][26][27][28][29]. The literature on TFP measurements has lately incorporated bad outputs.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strand of studies in the distance function framework is stochastic production frontier analysis (SFA), which includes a stochastic error term in the computation of the production possibility frontier, e.g., [8,18]. Finally, total factor productivity (TFP) is used in numerous studies [2,6,[19][20][21][22][23][24][25][26][27][28][29]. The literature on TFP measurements has lately incorporated bad outputs.…”
Section: Previous Researchmentioning
confidence: 99%
“…Studies analysing the pulp and paper industry include case studies of individual companies [5], industry-scale studies [7,22], and cross-country studies comparing effects on the manufacturing sector or general macroeconomic performance [14,16,25,40,41]. In addition to the studies focusing directly on the impact of environmental regulations on productivity and technical change, there are studies analysing the effects of environmental regulations on labour and capital productivity [6,38,42]; on investments and age of the capital stock [43,44]; and on industry profitability [7,30,45].…”
Section: Previous Researchmentioning
confidence: 99%
“…Alpay, Buccola, and Kerkvliet (2002) in a comparison of the US and Mexican food industries, found that when Mexico increased its pollution controls this lead to enhanced food production and productivity growth. , in a study of 4200 facilities in seven OECD countries, find evidence that environmental regulation induces innovation and that the costs of complying with this regulation are partially offset by this new innovation.…”
Section: Eco-innovation and Firm Performancementioning
confidence: 99%
“…The only cross-country study, Alpay et al (2002), similarly find no effect on adjusted productivity growth on the US food manufacturing sector, but a positive one in Mexico.…”
mentioning
confidence: 90%